The Efficacy of Haematococcus pluvialis Culture as a Bioremediator for Tofu Effluent - Putri, Dina Soes; Malik, Nina; Wangiyana, I Gde Adi Suryawan (Biota, 2025)
Wastewater management is one of the issues at the heart of the Sustainable Development Goals. This is urgent because waste that is not properly managed can cause damage to water bodies, reducing clean water sources that can be used for household, office and industrial needs. One of the low-cost yet effective wastewater management strategies which also produce valuable products is the use of microalgae as remediators to improve the quality of polluted waters. The aim of this study was to evaluate the efficiency of H. pluvialis culture as a bioremediator for tofu effluent. The research stages consisted of activation of H. pluvialis microalgal starter in Walne medium, followed by cultivation of microalgae in tofu effluent medium, observation of microalgal growth in the effluent, and measurement of water quality parameters such as pH, colour, BOD and COD, as well as the aroma of tofu effluent before and after use as a microalgal growth medium. According to the growth curve of H. pluvialis in the tofu wastewater medium, it is known that this microalgae can grow well in the effluent and can improve wastewater quality. Where the pungent odour typical of soya waste began to disappear from the second day of cultivation, the pH increased from acidic to neutral, and BOD and COD levels were drastically reduced. In conclusion, H. pluvialis microalgae can be used as a bioremidiator of tofu ffluent as it can effectively improve the quality of the wastewater.